Double-balloon catheter for induction of labor in 362 women with and without prior cesarean section - Anne B. Boisen; Ellen C. Løkkegaard; Jens Fuglsang (Elsevier, 2019)
Objective: Balloon catheter is the preferred method for induction of labor in women with prior cesarean section. We sought to evaluate the rate of vaginal delivery, induction-delivery time and outcome predictors after induction with double-balloon catheter. Study design: We conducted a retrospective cohort study including women with prior cesarean section undergoing induction of labor with a double-balloon catheter during the period January 2007-June 2014 at a large, tertiary Danish university hospital. For comparison, we included women with no prior cesarean section undergoing induction with double-balloon catheter after failed medical induction. Inclusion criteria were singleton pregnancy, an unfavorable cervix, intact membranes, cephalic presentation and either previous cesarean section or failed medical induction of labor. Exclusion criteria included contraindications for vaginal delivery, severe fetal malformation and stillbirth. Study subjects were identified in a local computerized system and data extracted from the medical records. Results: Women with prior cesarean section (n = 304) induced with double-balloon catheter had a vaginal delivery rate of 50.3% (95% CI 44.7-55.9) compared to 51.7% (95% CI 39.2-64.1) in women with no prior cesarean section but preceding failed medical induction of labor (n = 58) (p = 0.85). BMI≥30 was associated with increased frequency of cesarean section. Median time from induction to vaginal delivery was 27.1(20.4-31.1) hours and 28.4(25.5-36.1) hours, respectively (p = 0.05). The rate of complete uterine rupture was 1.0%. Conclusions: Similar success rates of approximately 50% for vaginal delivery were observed after induction of labor with a double-balloon catheter in women with and without prior caesarean section. A BMI ≥ 30 was associated with an increased frequency of caesarean section. Keywords: Double-balloon catheter, Induction of labor, Trial of labor after cesarean section, Vaginal birth after cesarean section